MENINGKATKAN KEMAMPUAN KOGNITIF (SAINS) MELALUI PEMBELAJARAN MENGENAL WARNA BERBASIS PEMANFAATAN LINGKUNGAN PADA ANAK USIA 4-5 TAHUN DI PAUD AFIFAH KIDS KABUPATEN KAMPAR - Tusiah, Tusiah; Indarto, Wusono; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This study aims to determine the increase in cogtive ability (science) through learning about colors based on use of the environment in children aged 4-5 years early chilhood kids Afifah Kampar District. This research using other research methodsclss action with the subject teacher and 15 childrens in the age group 4-5 years early childhood kids Afifah. The results of the data analysis of cognitive ability (scince) of children through learning about colors based on use of the environment shows that: The average increase of the pre-cycle to the first cycle of 28,44%, the average increase of cycle II cycle I of 42,91%, and the average increase of the pre-cycle of 83,55%. The shows that learningabouot colors based on the use of the enviorinment in improviong the cognitif abilities (scince)of children44-5 years in early chilhoo afifaf kids ups streamm up strem siak district, counteies experience a sinifikan increase.Keyword : cognitive abilities (science)